Development and Implementation of a Mass Balancing System for CubeSat Attitude Hardware-in-the-Loop Simulations - Ledo López, Guillermo (Luleå tekniska universitet, Rymdteknik, 2019)
Spacecraft simulator platforms can simulate the microgravity environment of space on Earth, for the purposes of testing the Attitude and Orbit Control Subsystem of satellites. In order to do this, the satellite is mounted on a bench and the combined center of mass of this assembly is controlled by a series of moving masses. The objective is to bring this center or mass as close as possible to the center of rotation, since solids in microgravity always rotate around their own center of mass. The air-bearing platform located, designed and built at the NanoSat Laboratory of the Kiruna Space Campus of the Luleå University of Technology makes use of four balancing masses, which are displaced by that number of linear actuators. This document explains the process followed to design an algorithm for the estimation of the center of mass and the subsequent calculation of the required positions of the balancing masses to bring this center of mass back to the center of rotation. First, the equations of rotational motion of the bench were found through two formulations: quaternions and Euler-Lagrange. Secondly, these equations were used to obtain an estimation of the center of mass via Batch Least-Squares. Thirdly, the equations of the center of mass of a system of point masses were used to find the proper positions of the balancing masses. Finally, the complete algorithm was tested with Hardware-in-the-Loop simulations before testing it in the real hardware of the platform. The developed algorithm was not capable of estimating the center of mass with sufficient accuracy, which invalidated the obtained actuator positions, and thus was not able to compensate the offset of the center of mass. Recommended lines of development are provided to assist on the continuation of this work.